Evaluation of a cognitive skills programme for male prisoners – exploring treatment effectiveness. Issue 4 (5th December 2016) - Ireland, Jane L.; Bates-Gaston, Jackie; Markey, Kevin; Greenwood, Leah; Ireland, Carol A.
Abstract : Purpose: The purpose of this paper is to provide an evaluation of a cognitive skills programme (Enhanced Thinking Skills) with adult prisoners. Design/methodology/approach: A pre- and post-treatment design with 171 male prisoners, using self-report psychometric measures. Findings: Significant differences were found in the direction expected. Clinical recovery using stringent methods was not indicated, although improvement/partial response was across a number of domains. Practical implications: Expectations for treatment outcome for short-term interventions should be more realistic; cognitive skills programmes may be best considered as precursors to longer term therapies; treatment outcome should focus on improvement and not recovery. Originality/value: This study represents the first prison study to distinguish between levels of positive change. It questions previous interpretations of treatment outcome.